Bacteria Isolated From the Antarctic Sponge Iophon sp. Reveals Mechanisms of Symbiosis in Sporosarcina, Cellulophaga, and Nesterenkonia - Moreno-Pino, Mario; Ugalde, Juan A.; Valdés, Jorge H.; Rodríguez-Marconi, Susana; Parada-Pozo, Génesis; Trefault, Nicole (Frontiers in Microbiology, 2021)
Antarctic sponges harbor a diverse range of microorganisms that perform unique metabolic functions for nutrient cycles. Understanding how microorganisms establish functional sponge–microbe interactions in the Antarctic marine ecosystem provides clues about the success of these ancient animals in this realm. Here, we use a culture-dependent approach and genome sequencing to investigate the molecular determinants that promote a dual lifestyle in three bacterial genera Sporosarcina, Cellulophaga, and Nesterenkonia. Phylogenomic analyses showed that four sponge-associated isolates represent putative novel bacterial species within the Sporosarcina and Nesterenkonia genera and that the fifth bacterial isolate corresponds to Cellulophaga algicola. We inferred that sponge-associated bacteria isolated inhabit similarly marine sponges and also seawater. Comparative genomics revealed that these sponge-associated bacteria are enriched in symbiotic lifestyle-related genes. Specific adaptations related to the cold Antarctic environment are features of the bacterial strains isolated here. Furthermore, we showed evidence that the vitamin B5 synthesis-related gene, panE from Nesterenkonia E16_7 and E16_10, was laterally transferred within Actinobacteria members. Together, these findings indicate that the genomes of sponge-associated strains differ from other related genomes based on mechanisms that may contribute to the life in association with sponges and the extreme conditions of the Antarctic environment.